2021
DOI: 10.51791/njap.v44i3.589
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of trypanosomosis and associated haematological changes among hunting dogs in Abeokuta, Nigeria

Abstract: African animal trypanosomosis (AAT) is one of the major constraints to the development of effective livestock production systems. Dogs are human companion and are believed to be sentinels for infection with the human species. This study was to detect subclinical and clinical infection of trypanosomes among hunting dogs in Abeokuta and its environs using molecular technique. A total of 87 dogs comprising of 49 males and 38 females were ramdomly screened for trypanosomes by polymerase chain reaction technique. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previous studies at other sites have shown higher diversity and prevalence of parasites among hunting dogs compared to non-hunting but free roaming dogs [ 52 , 53 , 56 , 57 ]. In addition, hunting dogs with higher parasitic loads have been shown to exhibit higher WBC and eosinophil counts [ 51 , 55 , 58 ]. Therefore, we hypothesized that hunting dogs would differ significantly from non-hunting dogs in WBC, strongyle-type ova, and eosinophil counts, but did not predict the direction of this relationship.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies at other sites have shown higher diversity and prevalence of parasites among hunting dogs compared to non-hunting but free roaming dogs [ 52 , 53 , 56 , 57 ]. In addition, hunting dogs with higher parasitic loads have been shown to exhibit higher WBC and eosinophil counts [ 51 , 55 , 58 ]. Therefore, we hypothesized that hunting dogs would differ significantly from non-hunting dogs in WBC, strongyle-type ova, and eosinophil counts, but did not predict the direction of this relationship.…”
Section: Methodsmentioning
confidence: 99%